COVERAGE OFPHYSICALFITNESSANDCONDmONING ACTIVITIES INPHYSICALEDUCATION CURRICULUMIN SECONDARY SCHOOLS: A PATHWAY FOR HEALH PROMOTION IN NIGERIA - Aniodo, D. A.; Eze, G (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
The main thrust of this study was to determine the extent of coverage of physical fitness and conditioning activities in physical education curriculum in secondary schools in Nigeria using Nsukka education zone as area of the study. It was also to point out how it can serve as a means of health promotion. The sample for the study consists of 220 physical Education teachers and students at the junior secondary level in Nsukka Education Zone of Enugu State. All the 72 physical education teachers and 148 junior secondary school students made up the sample, for this study. The data-gathering instrument for this study was a checklist and questionnaire titled Junior Secondary School Curriculum Coverage Questionnaire (JSSCUQUE) developed by the researchers based on literature review and personal experience. The questionnaire was made up two sections: A and B. Section A sought for demographic information from the respondents while section B elicited from the respondents information on the curriculum coverage associated with physical fitness and conditioning. Three experts in Department of Health and Physical Education, University of Nigeria Nsukka validated the instrument. The split-half method was used to establish the reliability of the instrument which was carried at a time lag of two weeks using twenty four teachers from Obollo Education Zone. The items were selected into even and odd number items. The responses of the two groups were ana lysed to establish the reliability co-efficient of the entire instrument using Spearman-Brown Correlation formula. The acceptable co-efficient was. 78. The mean and standard deviation was used for the purposes of description and in order to answer the research questions. The t-test, Anova and scheffe multiple comparisons test statistic wen! used to verify the null hypothesis. All the hypotheses were tested at. 05 level of sirpUJic~e'JUingthe t-test statistics. It was found that coverage of physical fitness and body conditioning in the physical education curriculum is of a moderate extent. Two of the three hypotheses tested were rejected while one was retained.; The study concluded that physical fitness and conditioning activities are covered in the physical education curriculum. It was therefore recommended that physical fitness and conditioning should be encouraged the more as a way of promoting health.